Assessing The Relationship Of Creativity Domains With Personality Traits, Academic Environment, And Academic Achevment Among Malaysian Undergraduate Students - Awawdeh, Malek Nassar Abdallah (2021)
This study aimed to develop a valid and reliable creative person assessment model to investigate the relationship of creativity domains (self/everyday, scholarly, performance, mechanical/scientific and artistic) with personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience), academic environment (students development, social relations, year of study, and type of school), and academic achievement CGPA among undergraduate Malaysian higher education students. There were 436 (253 responded through online and 183 responded the survey form) undergraduate students involved in this study. 21 respondents were deleted due to missing data or answering incorrectly. Therefore, the final size of the sample accredited for analysis purposes is 415 students from four schools in Universiti Sains Malaysia. Data was collected using three adopted self-scale reports to measure the constructs, namely the Kaufman domains of creativity scale (K-DOCS) to assess the creativity domains, the Big Five Inventory (BFI) to assess personality traits, and the college student experience questionnaire (CSEQ) to assess higher education environment. Data were analyzed using PLS-SEM in SmartPLS. The model has proven to be valid and reliable in the term of construct reliability, convergent validity, discriminant validity, and xv goodness of fit. The relationship between the exogenous variables and endogenous variables were significant. Personality traits were significantly correlated with creativity domains. The study provided empirical evidence for the relationship between the academic environment and creativity domains. Students’ academic achievement (CGPA) was found to be significantly correlated with four creativity domains. This study contributes to the literature by using SEM which provides a better understanding of conflicting results in creativity research, and by adding the academic environment to the traditional previous studies that were limited to personality traits.